The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/s00122-002-1031-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting EST databases for the development and characterization of gene-derived SSR-markers in barley (Hordeum vulgare L.)

Abstract: A software tool was developed for the identification of simple sequence repeats (SSRs) in a barley ( Hordeum vulgare L.) EST (expressed sequence tag) database comprising 24,595 sequences. In total, 1,856 SSR-containing sequences were identified. Trimeric SSR repeat motifs appeared to be the most abundant type. A subset of 311 primer pairs flanking SSR loci have been used for screening polymorphisms among six barley cultivars, being parents of three mapping populations. As a result, 76 EST-derived SSR-markers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

96
1,609
15
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,135 publications
(1,773 citation statements)
references
References 37 publications
96
1,609
15
7
Order By: Relevance
“…Of these, 897 primer pairs (84.6%) yielded amplicons in the two parents of our mapping population. This result was similar to EST-SSR amplification rate in sweetpotato [26,28] and many other studies in which a success rate of 60-90% amplification has also been reported [37,40-43]. In those studies (except [26]), they also reported a similar success rate of amplification for both genomic SSRs and EST-SSRs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Of these, 897 primer pairs (84.6%) yielded amplicons in the two parents of our mapping population. This result was similar to EST-SSR amplification rate in sweetpotato [26,28] and many other studies in which a success rate of 60-90% amplification has also been reported [37,40-43]. In those studies (except [26]), they also reported a similar success rate of amplification for both genomic SSRs and EST-SSRs.…”
Section: Discussionsupporting
confidence: 90%
“…The previous studies of arabidopsis [33] and soybean [35] also suggested that the tri-nucleotide AAG motif may be common motif in dicots. In contrast, the most frequent tri-nucleotide repeat motifs were (AAC/TTG)n in wheat, (AGG/TCC)n in rice, and (CCG/GGC)n in maize, barley and sorghum [31,36,37]. The abundance of the tri-nucleotide CCG repeat motif was favored overwhelmingly in cereal species [31,36,38] and also considered as a specific feature of monocot genome, which may be due to the high GC content and consequent codon usage bias [5,39].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting sequences were clustered using CAP3 (Huang and Madan 1999). Microsatellites were identified in ESTs using MISA (Thiel et al 2003) with its default parameters except that mononucleotides were not included in the search parameters. The primers were designed using Primer 3 (Rozen and Skaletsky 2000).…”
Section: Methodsmentioning
confidence: 99%
“…SSRs were mined in the genome sequence using the MIcroSAtellite (MISA) 52 program, with the following parameters: at least ten repeats for mono-, six repeats for di-, and five repeats for tri-, tetra-, penta-and hexa-nucleotide for simple SSRs. The Primer3 program 53 was used for designing the primer pairs for identified SSRs based on the following criteria: (i) annealing temperature (Tm) between 50-65 Ā°C with 60 Ā°C as optimum; (ii) product size ranging from 100 bp to 350 bp; (iii) primer length ranging from 18 bp to 24 bp with an optimum of 20 bp; (iv) GC % content in the range of 40-60%.…”
Section: Npgmentioning
confidence: 99%